Azido-Containing Diketo Acid Derivatives Inhibit Human Immunodeficiency Virus Type 1 Integrase In Vivo and Influence the Frequency of Deletions at Two-Long-Terminal-Repeat-Circle Junctions - Svarovskaia, Evguenia S. (American Society for Microbiology, 2004)
We previously found that azido-containing β-diketo acid derivatives (DKAs) are potent inhibitors of human immunodeficiency virus type 1 (HIV-1) integrase (IN) (X. Zhang et al., Bioorg. Med. Chem. Lett., 13:1215-1219, 2003). To characterize the intracellular mechanisms of action of DKAs, we analyzed the antiviral activities of two potent azido-containing DKAs with either a monosubstitution or a disubstitution of azido groups, using single- and multiple-replication-cycle assays. Both azido-containing DKAs significantly inhibited HIV-1 infection in 293T, CEM-SS, and H9 cells (50% inhibitory concentration = 2 to 13 μM) and exhibited low cytotoxicity (50% cytotoxic concentration = 60 to 600 μM). Inhibition of HIV-1 IN in vivo was demonstrated by the observation that previously described L-708,906 resistance mutations in HIV-1 IN (T66I and T66I/S153Y) also conferred resistance to the azido-group-containing DKAs. In vitro assays and in vivo analysis indicated that the DKAs did not significantly inhibit the 3′ processing and selectively inhibited the strand transfer reaction. In addition, quantitative PCR indicated that two-long-terminal-repeat (2-LTR) circles were elevated in the presence of the azido-containing DKAs, confirming that HIV-1 IN was the intracellular target of viral inhibition. To gain insight into the mechanism by which the DKAs increased 2-LTR-circle formation of 3′-processed viral DNAs, we performed extensive DNA sequencing analysis of 2-LTR-circle junctions. The results indicated that the frequency of deletions at the circle junctions was elevated from 19% for the untreated controls to 32 to 41% in the presence of monosubstituted (but not disubstituted) DKAs. These results indicate that the structure of the DKAs can influence the extent of degradation of viral DNA ends by host nucleases and the frequency of deletions at the 2-LTR-circle junctions. Thus, sequencing analysis of 2-LTR-circle junctions can elucidate the intracellular mechanisms of action of HIV-1 IN inhibitors.